Characterisation of Silver Deposited Coir Fibers by Magnetron Sputtering - Chandy, Melvi; Sarma, U. S.; Latha, M. S.; Kumar, K. Shreekrishna (International Coconut Community Journal, 2015)
Silver thin films are extensively used due to their superior optical, electrical and antimicrobial properties. Recent development in the incorporation silver thin films on natural fibers makes it possible to utilize its excellent physical and chemical properties in the field of textiles. Present study focuses on the surface functionalization of natural coir fiber with silver thin film by magnetron sputtering. This will help to widen the use of natural coir fibers. The surface morphology of the coated coir fibers are investigated by employing a scanning electron microscope. The results show that the surface functionalization of silver-coated coir fibers are highly versatile, and it possess excellent protection against ultraviolet radiation, exhibit excellent hydrophobicity (contact angle=105.2°) and good antibacterial effects. This study demonstrates that treatment, which uses silver thin films by magnetron sputtering, is a promising method for achieving multifunctional coir fabrics.